2023
DOI: 10.15244/pjoes/158765
|View full text |Cite
|
Sign up to set email alerts
|

The High Phosphorus Incorporation Promotes the Soil Enzymatic Activity, Nutritional Status, and Biomass of the Crop

Abstract: Phosphorus (P) application in the soil improves soil fertility and thus contributes to reproductive organ development, resulting in a higher cotton yield. However, the effect of increasing phosphorus rate on soil nutrient status, phosphorus-related enzyme activities, and its effects on crop productivity needs excellent attention. A consecutive two-year (2017-2018) field experiment containing three phosphorus levels [0 (P1), 100 (P2), and 200 (P3) kg P 2 O 5 ha -1 ] was accomplished by maintaining three replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In summary, both plant species (W. trilobata and W. chinensis) were correlated positively and negatively with each other under low and normal N conditions in terms of shoot length, root length, biomass, and physiological parameters. The PCA biplot and Pearson correlation essay indicated that W. trilobata has strong physiological parameters to adjust its normal growth under low-N conditions compared with W. chinensis, which agrees with the idea of Iqbal et al [60], who described the Pearson correlation and PCA analysis under different N conditions with different physiological parameters in different crops.…”
Section: Alleviation Of Ros By Defensive Antioxidant Enzyme Activitiessupporting
confidence: 87%
“…In summary, both plant species (W. trilobata and W. chinensis) were correlated positively and negatively with each other under low and normal N conditions in terms of shoot length, root length, biomass, and physiological parameters. The PCA biplot and Pearson correlation essay indicated that W. trilobata has strong physiological parameters to adjust its normal growth under low-N conditions compared with W. chinensis, which agrees with the idea of Iqbal et al [60], who described the Pearson correlation and PCA analysis under different N conditions with different physiological parameters in different crops.…”
Section: Alleviation Of Ros By Defensive Antioxidant Enzyme Activitiessupporting
confidence: 87%
“…Grazing and mowing are generally reported to increase soil bulk density [15,34], and our results add to these findings. This increase in soil bulk density might be due to force applied on the soil surface by livestock trampling and mowing machines by increasing soil mechanical resistance and compaction, reduction in soil infiltration, and aggregate stability [3,4,15,35]. The effect of grazing and mowing on soil bulk density may also vary with respect to ecological factors, soil type, and seasons.…”
Section: Grazing/mowing and Soil Chemical Propertiesmentioning
confidence: 99%
“…High intensity of grazing decreases soil moisture and facilitates soil erosion [2]. Livestock trampling affects soil by increasing mechanical resistance, hence altering soil bulk density [3], water infiltration, soil porosity, and aggregate stability [4]. In contrast, soil compaction is often adversely linked with the content of soil organic matter and root growth; soil bulk density may vary for soil's different layers, duration, and grazing intensity [5].…”
Section: Introductionmentioning
confidence: 99%
“…These leaf/plant functional traits closely linking to ecophysiological processes and production could be driven by biotic factors such as genetic variation (e.g., [ 10 ] ) and metabolite biosynthesis [ 34 , 35 ], and abiotic factors such as soil nutrition [ 36 40 ] and soil pollution [ 41 43 ]. Leaf functional traits are largely reshaped by the local climate over millennia [ 4 ].…”
Section: Introductionmentioning
confidence: 99%